Segurança dos ciclistas: uma abordagem analítica - Santos, Stefano Amaral Bispo (Universidade Federal de São Carlos, 2023)
The purpose of this work is to conduct a study on general instruments that allow and ensure cyclist safety in urban spaces, analyzing what is already implemented and what can still be done, and looking for ideal scenario for this type of system user. In this way, existing methods and infrastructure that guarantee their safety were qualitatively and analytically evaluated. The analysis was based on articles and manuals related to the topic. Also, through a form, qualitative data was obtained regarding how safe cyclists felt when traveling their route, as well as infrastructure questions. Therefore, the aim is to identify improvements to be made in urban spaces, especially in Brazil, so that cyclists can really have their safety guaranteed and bicycle transportation is increasingly used. Through the analysis of the collected data, it was possible to perceive the country's cycle infrastructure, although there is a certain bias in the data due to the number of respondents and their location. Based on the collected data, it was determined that when the traffic region does not have a cycle lane or cycle track, users feel less safe. It is clear that infrastructure has great relevance in this regard. To make people feel more comfortable and safe when cycling, adequate infrastructure is necessary, with a cycle lane and/or cycle track with proper signaling.
Cyclists' safety: an analytical approach
Keywords: Segurança do ciclista; Espaço urbano; Infraestrutura; Trânsito; Bicicleta; Mobilidade Urbana; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::PLANEJAMENTO DE TRANSPORTES::PLANEJAMENTO E ORGANIZACAO DO SISTEMA DE TRANSPORTE